Evaluation of the combined solar TiO2/photo-Fenton process using multivariate analysis - Nogueira, Raquel Fernandes Pupo [UNESP]; Trovó, A. G. [UNESP]; Paterlini, W. C. [UNESP] (My University, 2004)
The effect of combining the photocatalytic processes using TiO 2 and the photo-Fenton reaction with Fe3+ or ferrioxalate as a source of Fe2+ was investigated in the degradation of 4-chlorophenol (4CP) and dichloroacetic acid (DCA) using solar irradiation. Multivariate analysis was used to evaluate the role of three variables: iron, H2O2 and TiO2 concentrations. The results show that TiO2 plays a minor role when compared to iron and H2O2 in the solar degradation of 4CP and DCA in the studied conditions. However, its presence can improve TOC removal when H2O2 is totally consumed. Iron and peroxide play major roles, especially when Fe(NO3)3 used in the degradation of 4CP. No significant synergistic effect was observed by the addition of TiO 2 in this process. On the other hand, synergistic effects were observed between FeOx and TiO2 and between H 2O2 and TiO2 in the degradation of DCA. © IWA Publishing 2004.
Keywords: 4-chlorophenol; Dichloroacetic acid; Multivariate analysis; Photo-Fenton; TiO2; Acetic acid; Concentration (process); Degradation; Hydrogen; Iron; Irradiation; Multivariable control systems; Solar energy; Titanium dioxide; Photo-Fenton process; Synergistic process; Photocatalysis; 4 chlorophenol; dichloroacetic acid; ferrous ion; hydrogen peroxide; iron derivative; nitric acid derivative; oxalic acid derivative; titanium dioxide; Fenton reaction; phenol; photochemical treatment; wastewater treatment; aqueous solution; chemical analysis; concentration (parameters); controlled study; dechlorination; degradation kinetics; multivariate analysis; photocatalysis; photodegradation; solar radiation; total organic carbon; waste water management; Chlorophenols; Coloring Agents; Dichloroacetate; Hydrogen Peroxide; Multivariate Analysis; Photochemistry; Root Canal Irrigants; Sunlight; Titanium; Water Pollutants; Water Purification